Netmes: Assessing Gene Network Inference Algorithms by Network-Based Measures. (January 2014) - Altay, Gökmen; Kurt, Zeyneb; Dehmer, Matthias; Emmert-Streib, Frank
Gene regulatory network inference (GRNI) algorithms are essential for efficiently utilizing large-scale microarray datasets to elucidate biochemical interactions among molecules in a cell. Recently, the combination of network-based error measures complemented with an ensemble approach became popular for assessing the inference performance of the GRNI algorithms. For this reason, we developed a software package to facilitate the usage of such metrics. In this paper, we present netmes, an R software package that allows the assessment of GRNI algorithms. The software package netmes is available from the R -Forge web sitehttps://r-forge.r-project.org/projects/netmes/ .